2022
DOI: 10.1002/wat2.1602
|View full text |Cite|
|
Sign up to set email alerts
|

Examining water and gender narratives and realities

Abstract: There is a wealth of scholarly knowledge that aims to disentangle the complex relationship between gender and water. This scholarship coupled with practitioners' collective experiences and insights have resulted in the emergence of certain narratives that describe how unequal gender relationships to water are manifested and how they can be addressed. In this paper, we critically examine four of these water and gender narratives, myths, or realities: Are women solely responsible for water collection? Are women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Observed differences are even more pronounced for women. These results align with existing research documenting persistent gender differences in water access and concern globally (Harris et al 2017;Dickin and Caretta 2022), but this finding could also reflect differential risk perception/reporting of impacts as has been found in several previous studies (Mooney et al 2021). While very limitedly represented in our survey and therefore subject to significant uncertainty, genderqueer and non-binary individuals have the highest rate of reported household water supply impacts (77%).…”
Section: Discussionsupporting
confidence: 91%
“…Observed differences are even more pronounced for women. These results align with existing research documenting persistent gender differences in water access and concern globally (Harris et al 2017;Dickin and Caretta 2022), but this finding could also reflect differential risk perception/reporting of impacts as has been found in several previous studies (Mooney et al 2021). While very limitedly represented in our survey and therefore subject to significant uncertainty, genderqueer and non-binary individuals have the highest rate of reported household water supply impacts (77%).…”
Section: Discussionsupporting
confidence: 91%
“…Considerable time is spent on procuring water: for example, a study in Los Angeles found that unhoused people spent up to 2 h trying to access water services (Avelar Portillo, 2021). Research shows that when households lack convenient water supply, the burden of procuring, transporting, and managing water falls disproportionately on women and children (Dickin & Caretta, 2022) and the emerging literature thus far indicates the same is true for unhoused communities (DeMyers et al, 2017).…”
Section: Key Definitions and Insightsmentioning
confidence: 99%
“… 1 2 Due to gendered norms and practices related to water, women and girls bear the burden of water fetching and management within the household in many countries. 3 4 This is linked to health outcomes such as musculoskeletal injuries, 5 psychosocial stress 6 7 and gender-based violence. 8 This unpaid work can also be extremely time-consuming, constraining time for productive, educational or leisure activities.…”
Section: Introductionmentioning
confidence: 99%
“…Poor access to water, sanitation and hygiene (WASH) services threatens public health and contributes to gender and social inequalities 1 2. Due to gendered norms and practices related to water, women and girls bear the burden of water fetching and management within the household in many countries 3 4. This is linked to health outcomes such as musculoskeletal injuries,5 psychosocial stress6 7 and gender-based violence 8.…”
Section: Introductionmentioning
confidence: 99%